Processo penal e deformidades no sistema garantista: perspectiva de gênero, violência sexual e revitimização - Cardozo, Mayra Jardim Martins (2024)
This research explores the intricate intersection between the garantist penal system and gender issues, focusing specifically on sexual violence against women and the dynamics of procedural revictimization. The study employs a qualitative approach, centering on documentary analysis of legislation, relevant feminist legal theory literature, case law, and case studies to understand how gender biases and cultural stereotypes impact the administration of justice. It argues that although the garantist system is designed to protect the rights of the accused, it often fails to adequately protect victims of sexual violence, contributing to their revictimization. Structured in five chapters, the analysis ranges from the implementation of gender perspectives in the Democratic Rule of Law and the effectiveness of law as an emancipatory tool in combating institutional gender violence, to the impact of the Inter-American Human Rights System on the protection of women's rights. The final chapters detail the reality of sexual violence in Brazil and the deformities of the garantist system from a gender perspective, proposing procedural reforms for fairer and more equitable justice. This dissertation significantly contributes to the dialogue on penal reforms, emphasizing the need for a revision of judicial practices in light of contemporary gender realities